民族地區地方課程建構的基本理念與實踐策略 Idea and Strategy of Local Curriculum Construction in Minority Region in China - 王巧玲Qiao-Ling Wang (Higher Education Foundation, 2009)
民族地區地方課程建構的基本理念應是：地方課程建構為實現少數民族文化傳承與發展服務。其要點有：地方課程建構為尊重當地居民發展需求和根本利益服務；地方課程建構為在保護少數民族文化基礎上實現「適應性」創新服務；地方課程建構為著力激發當地居民的文化自覺服務。民族地區地方課程的開發模式應是「綜合性課程」開發模式。民族地區地方課程內容的文化選擇標準應是：注重少數民族文化的整體性、凸顯少數民族文化特質、適時體現世界多元文化、追逐少數民族文化的時代發展。 民族地區地方課程建構的實踐策略應是：在課程開發歷程方面，應將當地需求作為核心；在課程內容開發方面，可將可持續發展價值觀作為邏輯架構的獨特視點；在課程性質定位方面，要將體驗課程付諸實踐；在課程目標確立方面，應將價值觀目標、技能目標和行為目標並重。 Three basic ideas of local curriculum construction in minority region are put forward: Local curriculum construction should service for the development of ethnic minorities' traditional culture; Model of local curriculum development should be "Integrated" development model; The cultural choice of local curriculum should pay special attention to cultural traits & integrity of culture & diversification & modern features. Three practice strategies of local curriculum construction in minority region include as follows: Special view of the logical construction is value of sustainable development; Experienced curriculum is put into practice; Equal stress was laid on the objects of value and behavior.